KEMAMPUAN MENYIMPULKAN TEKS EKSPOSISI BERDASARKAN GAGASAN UTAMA DAN UNSUR FAKTA PADA SISWA KELAS VIII MTS MAMIYAI MEDAN TAHUN PEMBELAJARAN 2024/2025 - Yasmin Salsabila Siagian; Khairil Ansari (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to describe the ability to conclude exposition texts based on main ideas and factual elements in class VIII students of MTs Mamiyai Medan in the 2024/2025 Academic Year. The population in this study were all class VIII students of MTs Mamiyai Medan with a total of 141 students. The research sample was 35 students. The method used was quantitative descriptive. The results of this study indicate that the ability of class VIII students of MTs Mamiyai Medan in concluding exposition texts is included in the good category with an average score of 73.4. The main idea aspect of 80% is in the good category, the factual element aspect of 68.5% of students is in the fairly good category, the linguistic aspect of 54.2% of students is in the fairly good category, the understanding aspect of 60% of students is in the fairly good category. Of all the aspects assessed, the ability to conclude exposition texts based on main ideas and factual elements in class VIII students of MTs Mamiyai Medan in the 2024/2025 academic year is good.